Moving from web services to an enterprise service-based architecture act now to expand your business capabilities. - Zurek, Bob
Today's software industry is moving fast to supply innovative technologies, new standards and early customer case studies targeted at fulfilling the vision of Web services. But as these products, standards and customers emerge, it is now time to move beyond using the simple term Web services-it really misrepresents what is starting to take shape in today's enterprise, the emergence of the enterprise service-based architecture.